Aspects for Graph Grammars - Machado, Rodrigo; Foss, Luciana; Ribeiro, Leila (Electronic Communications of the EASST, 2009)
Aspect-oriented programming (AOP) is an extension to the object oriented paradigm that aims to provide better modularity for code that is usually scattered across an object-oriented system such as logging, authentication and distributed object handling. Aspect weaving is a novel way to compose systems, focusing on the integration of system-wide policies through pattern-action rules. While there are several semantic proposals for representing aspects over source code and programs, aspect weaving for visual models such as graph rewriting systems is still not fully established. In this work, we propose the definition of aspect-oriented graph grammars, an extension to conventional graph grammar where aspects are modeled as transformation rules over the structure of a base graph grammar.